The displacement coefficient method in near‐source conditions. (20th October 2014) - Baltzopoulos, Georgios; Chioccarelli, Eugenio; Iervolino, Iunio
Summary The use of nonlinear static procedures for performance‐based seismic design (PBSD) and assessment is a well‐established practice, which has found its way into modern codes for quite some time. On the other hand, near‐source (NS) ground motions are receiving increasing attention, because they can carry seismic demand systematically different and larger than that of the so‐called ordinary records. This is due to phenomena such as rupture forward directivity (FD), which can lead to distinct pulses appearing in the velocity time‐history of the ground motion. The framework necessary for taking FD into account in probabilistic seismic hazard analysis (PSHA) has recently been established. The objective of the present study is to discuss the extension of nonlinear static procedures, specifically the displacement coefficient method (DCM), with respect to the inelastic demand associated with FD. In this context, a methodology is presented for the implementation of the DCM toward estimating NS seismic demand, by making use of the results of NS‐PSHA and a semi‐empirical equation for NS‐FD inelastic displacement ratio. An illustrative application of the DCM, with explicit inclusion of NS‐pulse‐like effects, is given for a set of typical plane R/C frames designed under Eurocode provisions. Different scenarios are considered in the application and nonlinear dynamic analysis results are obtained and discussed with respect to the static procedure estimates. Conclusions drawn from the results may help to assess the importance of incorporating NS effects in PBSD. Copyright © 2014 John Wiley & Sons, Ltd.